Synthesis and Crystal Structure of a New Complex: [phen2Co]2·Mn(SCN)6·4H2O - Bi, Jian-Hong; Li, Bai-Zhong; Huang, Zi-Xian; Li, Jian (Asian Journal of Chemistry, 2010)
A novel cobalt(II) complex [phen 2Co]2·Mn(SCN)6·4H2O, where phen is 1,10-phenanthroline,a = 90º, b = 95.743(3)º, g = 90º, V = 3809.7(13) Å3, Z = 2, Mr =3, μ = 0.821 mm-1, F(000) = 1714, T = 293(2) K, R = 0.0676, wR =s(I). The crystal structure analysis shows that the cobalt(II) was synthesized and characterized by IR spectra, elemental analysis and single-crystal X-ray. The crystal is monoclinic, space group P2(1)/n with unit cell parameters: a = 10.261(2) Å, b = 19.549(4) Å, c = 19.088(4) Å, 761.06, Dc = 1.460Mg/cm 0.2057 for 29078 reflections with I > 2 is a six-coordinated in a slightly distorted octahedron environment.